Plasma Protein Biomarkers and Long‐Term Cardiovascular Mortality Risk in Patients With Chronic Coronary Heart Disease - Ralph A. H. Stewart; Kristy P. Robledo; Andrew M. Tonkin; Anthony Keech; Leonard Kritharides; Ian Marschner; Edward Janus; Peter L. Thompson; Gerald F. Watts; Tanja Zeller; Harvey D. White; John Simes (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Protein biomarkers that reflect different pathophysiological pathways have been associated with the risk of adverse cardiovascular events. However, it is uncertain whether these associations are sustained with increasing years after the biomarkers are measured. Methods and Results In this cohort study, 7745 patients with coronary heart disease who participated in the LIPID (Long‐Term Intervention With Pravastatin in Ischemic Disease) trial, BNP (B‐type natriuretic peptide), troponin I, cystatin‐C, C‐reactive protein, d‐dimer and midregional proadrenomedullin were measured at baseline and after 1 year. Discrimination of plasma biomarker concentrations for cardiovascular death were evaluated in landmark analyses from 1 year for the next 5 years of the randomized trial, and for 10 additional years after trial completion. All 6 biomarkers were associated with risk of cardiovascular death (n=1903) both during and after the clinical trial (each P<0.001). C‐statistics for BNP were 0.706 and 0.704; cystatin‐C, 0.686 and 0.693; troponin I, 0.686 and 0.689; C‐reactive protein, 0.655 and 0.684; d‐dimer, 0.670 and 0.679, and midregional adrenomedullin, 0.686 and 0.688, respectively. In multivariable models, adding all 6 biomarkers to models with clinical risk factors increased the C‐statistic for cardiovascular death from 0.709 to 0.775 during the clinical trial, and from 0.713 to 0.751 during 10‐year follow‐up after the randomized trial (P<0.001 for both). Conclusions In patients with chronic coronary heart disease, biomarkers that reflect different pathophysiological pathways are associated with the risk of cardiovascular death for at least the next 15 years.